Traffic Impact Analysis of the Development of the Simalungun Regency Trade Market - Anggiat Sinurat; M.Arief Kurniawan; Pawer Darasa Panjaitan; Rudi Salam; Juniar Batubara; Bilson Panjaitan (Journal of Public Representative and Society Provision, 2026)
This study aims to analyze the magnitude of the impact or influence caused by the Trading Market development activities, which can affect traffic performance in the surrounding area so as to minimize the impact on traffic disruption. This study uses initial calculations carried out to find the peak hour (pcu/hour), namely by changing the traffic volume data that is still in units of vehicles/hour, then multiplied by the passenger car equivalent factor (pcu). The value of the passenger car equivalent factor (pcu) refers to the Indonesian Road Capacity Guidelines (PKJI) 20223. The results show the degree of saturation of the new market road segment 2 at the highest peak hour of the existing condition is 0.55, during the construction period of 2024 is 0.60. During the operational period of 2025 is 0.57 and the prediction of 5 (five) years in 2030 is 0.67. The degree of saturation of the new market road segment 1 at the highest peak hour of the existing condition is 0.08, during the construction period of 2024 is 0.09. During the operational period of 2025 is 0.09 and the prediction of 5 (five) years in 2030 is 0.11. The degree of saturation of the Rajamin Purba road segment 1 at the highest peak hour of the existing condition is 0.86, during the construction period of 2024 is 0.88, During the operational period of 2025 is 0.89 and the prediction of 5 (five) years in 2030 is 1.05. The degree of saturation of Rajamin Purba road segment 2 during the highest peak hour in existing conditions is 0.86, during the construction period in 2024 it is 0.91, during the operational period in 2025 it is 0.88 and the 5 (five) year prediction in 2030 is 0.99.